Psychiatric disorders in adults with cerebral palsy. (April 2021) - McMorris, Carly A.; Lake, Johanna; Dobranowski, Kristin; McGarry, Caitlin; Lin, Elizabeth; Wilton, Drew; Lunsky, Yona; Balogh, Robert
Abstract: Background: Cerebral palsy (CP) is one of the most common neurological conditions in childhood. Individuals with CP often experience various secondary conditions, including intellectual disability (ID), medical conditions, and psychiatric issues. A large number of youth with CP have psychiatric disorders; however, few studies have examined the prevalence of psychiatric issues in adults with CP at the population-level. Aims: To investigate the prevalence and co-occurrence of psychiatric disorders at the population-level in adults with CP only, and adults with CP and ID. Method and procedures: Using clinical information from seven Canadian data sources, we conducted a retrospective cross-sectional analysis of adults with CP, with and without ID. Outcomes and results: Adults with CP were more likely than the general population to have a psychiatric diagnosis, independent of ID status. All psychiatric disorders were more common in individuals with CP than the general population, with the exception of addiction related disorders. In most cases, having an ID substantially increased the risk of having a psychiatric disorder. Conclusions: Adults with CP are at heightened risk for experiencing psychiatric disorders. Current findings highlight the important role health care providers play in screening for psychiatric issues in individuals with CP.